Tending and Logic between Bardili and Hegel: The Operativity of Reason beyond the Philosophy of the Subject - Ferraguto, Federico (ETHICS IN PROGRESS, 2025)
The paper traces some stages in the process of the speculative emancipation of the Trieb in Post-Kantian philosophy with the aim of reconstructing the context that allows explaining the outcomes of the treatment given to it by Hegel in the Science of Logic. Initially, some elements that underlie the speculative assimilation of the concept of Trieb in the course of the development of post-Kantian philosophy are presented, and in a second step, the position of an author central to the development of Hegel’s Logic, namely Christoph Gottfried Bardili, is discussed. The theory of the drive developed by Bardili in Grundriss der ersten Logik makes possible a clearer understanding of the different levels at which Hegel makes use of the notion of Trieb in the doctrine of the concept and particularly in the understanding of teleology developed in Wissenschaft der Logik. The overall purpose is to show how the debate on Trieb does not take the form of the evolution of a purely anthropological interpretation, oriented toward a supposed critique of ‘subjectivity’, but rather is the result of its integration in a speculative sense.